A Preliminary Study on the Effects of Black Cohosh Preparations on Bone Metabolism of Rat Models With GnRH-a-Induced Peri-Menopausal Symptoms - Qin, Zhenyue; Dong, Zhiyong; Liu, Junling; Zhong, Ahong; Bao, Mingyue; Wang, Huihui; Yu, Hongxia; Zhang, Shoufeng; Zhang, Wendi; Shen, Li; Wu, Jie; Chen, Jiming (Frontiers in Endocrinology, 2022)
Background Endometriosis (EMS) is a relapsing and estrogen-dependent disease. For endometriosis such as deep endometriosis and ovarian endometrioid cysts, surgery is the most effective treatment. Long-term follow-up showed that the recurrence rate of endometriosis after surgical treatment was high, so postoperative drugs were needed to reduce recurrence, and Gonadotropin-releasing hormone agonists (GnRH-a) was the most commonly used drug for postoperative management.GnRH-a may reduce the post-treatment endometriosis relapses by lowering the hormone levels in the body. However, the use of GnRH-a can give rise to perimenopausal symptoms, especially osteoporosis, bone loss, and bone pain, for which reason GnRH-a use is often limited. The add-back therapy is often used to alleviate the untoward effects caused by GnRH-a. However, long-term use of hormone drugs may lead to EMS recurrence, thrombosis, and breast cancer. Therefore, a safer and more effective drug is urgently needed to alleviate the untoward effects caused by GnRH-a. In recent years, scholars at home and abroad have found that isopropanolic Cimicifuga racemosa extract (ICR), as a plant extract, can better relieve the symptoms of perimenopausal women. At the same time, some studies have initially confirmed that black cohosh preparations can relieve the perimenopausal symptoms caused by GnRH-a treatment in EMS patients. Objective To investigate the effect of black cohosh preparations on the bone metabolism of rat models with GnRH-a-induced peri-menopausal symptoms． Methods The rat models of peri-menopausal symptoms were established by GnRH-a injection. and normal saline (NS injection) was used as the control. According to the modeling method and drug intervention, the rats were randomly divided into 4 groups: GnRH-a injection + saline intervention group (GnRH-a + NS), saline injection control + saline intervention group (NS + NS), GnRH-a injection + estradiol intervention group (GnRH-a + E2), and GnRH-a injection + black cohosh preparation intervention group (GnRH-a + ICR). The rat models were identified with the vaginal smear method, and then the corresponding drug intervention was administrated for 28 days. After the intervention, the rats were sacrificed. The rats' bone mineral Results (1)